Correlation between arterial and venous sodium and potassium values in critically ill patients by arterial blood gas and electrolyte analyzer attending tertiary hospital of Nepal - Bhusal, Pramila; Nepal, Suresh Prasad (Journal of General Practice and Emergency Medicine of Nepal, 2022)
Introduction: Electrolytes are elements and compounds that occur naturally in the body and control important physiological function. Electrolyte disorder occurs when the levels of electrolytes in the body are either too high or too low. The causes, severity, treatment, and outcomes can vastly differ depending on the implicated electrolyte imbalances. The objective of this study is to comprehend the correlation between sodium and potassium levels measured in critically ill patients attending a tertiary care hospital of Nepal.Method: This study was a hospital based prospective observational comparative study conducted in the Department of General Practice and Emergency Medicine, Bir hospital, Kathmandu, from June 2019 to December 2019. After fulfilling inclusion and exclusion criteria a total of 95 patients were included in the study. Data were entered and analyzed in SPSS 20. The findings were presented in figures and tables. Statistical analysis was done using appropriate formula. Mean, standard deviation and correlation coefficient were calculated.Result: The mean value of arterial sodium was 134.67mmol/L and venous sodium was 135.93mmol/L. The mean value of arterial potassium was 4.0mmol/L and venous potassium was 4.19mmol/L. The correlation coefficient obtained for sodium was 0.703 and for potassium was 0.436. There was positive correlation of arterial sodium and arterial potassium with venous sodium and venous potassium indicating agreement between the parameters.Conclusion: Arterial sodium and arterial potassium can be used instead of venous sodium and venous potassium levels in management of critically ill patients.